Pengaruh Belajar Kelompok dan Persepsi Siswa Tentang Kewirausahaan Terhadap Nilai Ulangan Akhir Semester I Mata Pelajaran Kewirausahaan Pada Kelas XI di SMK Prawira Marta Kartasura Tahun Ajaran 2014/2015 - Amaliya, Rizka; , Prof. Dr. Harsono, SU (2015)
This study was to determine: 1) Effect of group learning tehadap UAS I value entrepreneurship subjects in class XI in vocational Prawira Marta Kartasura 2014/2015 academic year. 2) The influence of students' perceptions about the value of entrepreneurship to the first UAS entrepreneurship subjects in class XI in vocational Butler Marta Kartasura academic year 2014/2015. 3) Effect of group learning and perceptions of students about entrepreneurship against the value of the first UAS entrepreneurship subjects in class XI in vocational Butler Marta Kartasura academic year 2014/2015. This research includes associative quantitative research whose conclusions obtained based on the statistical analysis. The population in this study were all students of class XI SMK Butler Marta Kartasura academic year 2014/2015, amounting to 100 students, a sample of the results of the entire population by using census techniques. Techniques of data collection questionnaire and documentation. Previous questionnaire has been tested with the validity and reliability test. Data analysis technique used to test the hypothesis is multiple linear regression analysis, t test and F test, test R2, and the relative contribution and effective contribution. Results of regression analysis regression equation Y = 66.909 + 0,100X1 + 0,137X2 which means the value of entrepreneurship subjects UAS I was influenced by learning groups and persesi students about entrepreneurship. Conclusion: 1) There is a group studying the effect on the value of entrepreneurship subjects UAS. Based on t test obtained t count> t table is 3.264> 1.984, and the significance value <0.05 is 0.02. 2) There is an effect on students' perceptions of the value of UAS first entrepreneurial entrepreneurship subjects. Based on test results obtained thiting t> t table, namely 3.059> 1.98 and a significance value <0.05 is 0.03. 3) There is the influence of group learning and perceptions of students about entrepreneurship against the value of the first UAS entrepreneurship subjects. Based on F test obtained nulai Fhitng> Ftable, ie 14.011> 3.07 and a significance value <0.05 is 0.000. 4) The variables studied groups contribute effectively amounted to 11.773%, the variable student perception of entrepreneurship contribute effectively amounted to 10.6305%, total effective contribution is 22.4%, so it can be said that the study group is more dominant influence UAS I value entrepreneurship subjects , 5) The result of the coefficient of determination (R2) of 0.224 indicates that the influence of group learning and perceptions of students about entrepreneurship against the value of the first UAS entrepreneurship subjects was 22.4% with the remaining 77.6% is influenced by other variables: Keywords: Learning group, perceptions of students about entrepreneurship, the end of the first half of replay value entrepreneurship subjects.